Knowledge, Attitude, Frequency and Level of Consumption Regarding Non-alcoholic Carbonated Soft Drinks among Students from Two High Schools in Hanoi, Vietnam in 2015 - Nguyen Thanh Ha; Le Thi Thu Ha; Luu Quoc Toan (AIMS Press, 2017)
Objective: This article aims to describe the knowledge, attitude, frequency and level of consumption regarding non-alcoholic carbonated soft drinks (NCSD) among students from two high schools in Hanoi. Materials and Methods: A cross-sectional survey including a semi-quantitative food frequency were conducted with 620 students from two high schools, one in the urban area and the other in the rural area of Hanoi city. Results: Data on knowledge of health risk associated with the consumption of NCSD showed neagtive results (only 11.9% of the students were able to identify all the contents of NCSD correctly, and 2.7% knew all eight health risks due to consumption of NCSD). Besides, 31.4% of all students did not have the intention to quit NCSD despite being aware of health risks associated with the consumption of NCSD. Students who reported consuming NCSD within one month prior to the study constituted 83.1%, and those who consumed NCSD 1-2 times/week accounted for the highest proportion, being 21.3%. On average, each student consumed 2,094 ml NCSD within one month prior to the study. Suburban students and male students consumed more than urban and female ones, respectively (p < 0.01). Recommendations: Students should be equipped with information about NCSD related health risks and encouraged to consume less NCSD.